PENGARUH SALES PROMOTION DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING - Endang Kurniawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The purpose of this study was to analyze the effect of Sales Promotion and Store Atmosphere on Impulse buying at Rabbani Banyumanik Semarang consumers. The population in this study were all consumers who bought Rabbani Banyumanik Semarang, the number of which was not known with certainty. While the samples taken were 100 people. The sampling technique used was purposive sampling. The data analysis tool used in this research is multiple regression analysis. Based on the results of the study: There is a positive and significant influence between Sales Promotion on Impulse buying, There is a positive and significant influence between Store Atmosphere on Impulse buying.